A simple and high -performance immobilization technique of membrane protein from crude cell lysate sample for a membrane-based immunoassay application. Issue 1 (2nd January 2023) - Khemthongcharoen, Numfon; Uawithya, Panapat; Yookong, Nutthapon; Chanasakulniyom, Mayuree; Jeamsaksiri, Wutthinan; Sripumkhai, Witsaroot; Pattamang, Pattaraluck; Juntasaro, Ekachai; Kamnerdsook, Ampol; Houngkamhang, Nongluck; Promptmas, Chamras
ABSTRACT: Membrane proteins are difficult to be extracted and to be coated on the substrate of the immunoassay reaction chamber because of their hydrophobicity. Traditional method to prepare membrane protein sample requires many steps of protein extraction and purification that may lead to protein structure deformation and protein dysfunction. This work proposes a simple technique to prepare and immobilize the membrane protein suspended in an unprocessed crude cell lysate sample. Membrane fractions in crude cell lysate were incorporated with the large unilamellar vesicle (LUV) that was mainly composed of POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) before coating in the polystyrene plate by passive adsorption technique. Immunofluorescence staining and the Enzyme-Linked Immunosorbent Assay (ELISA) examination of a strictly conformation-dependent integral membrane protein, Myelin Oligodendrocyte Glycoprotein (MOG), demonstrate that LUV incorporated cell lysate sample obviously promotes MOG protein immobilization in the microplate well. With LUV incorporation, the dose–response curve of the MOG transfected cell lysate coating plate can be 2–9 times differentiated from that of the untransfected cell lysate coating plate. The LUV incorporated MOG transfected cell lysate can be efficiently coated in the microplate without carbonate/bicarbonate coating buffer assistance.